Evaluation and Mapping of Disaster-Responsible and Resilient Villages in East Rembang - Hamid, Nur; Juhadi, Juhadi; Kasmuri, Kasmuri; Riyadi, Agus; Mahat, Hanifah; Hashim, Mohmadisa; Rohmah, Umi Amanatur; Aroyandini, Elvara Norma (Universitas Diponegoro, Indonesia, 2024)
Indonesia's development must be connected to the important role of village empowerment and disaster resilience. Efforts to increase village empowerment and resilience to disasters have been carried out previously, especially in villages in East Rembang. Even so, there has yet to be an evaluation to measure its success. This research aims to evaluate and map village empowerment and resilience using research instruments consisting of aspects, indicators, sub-indicators, and questions regarding disasters in East Rembang. The four main stages of research include instrument development, measurements of empowered and disaster-resilient villages that have been carried out, mapping of measurement results, and based on recommendations. The data collection technique used is a document study with the data collection instrument, namely a document study sheet containing a scale for measuring village empowerment and disaster resilience. The village empowerment scale was developed based on geographic, government, population, social, agricultural, economic, and housing aspects. In contrast, the disaster-resilient village scale consists of six aspects that reflect the value of security from disasters, facilities, and mitigation efforts. This research shows seven categories of villages that are empowered and resilient to disasters. The three villages with the highest level of empowerment are Sluke, Sendangmulyo, and Kragan Villages in Sluke, Sarang, and Kragan Districts, respectively. Meanwhile, the three villages with the highest disaster resilience are Sanetan, Bendo and Langgar Villages, Sluke District.